Demagnetisation optimisation of ring winding axial flux permanent magnet motor by modifying the load line of the magnet - Farshid Mahmouditabar; Abolfazl Vahedi; Noureddine Takorabet (IET Electric Power Applications, 2023)
Abstract Recently the new topologies of the permanent magnet (PM) motor attract a lot of attention. These newly introduced PM motors are not mature in design aspects and suffer from different perspectives. Therefore, it is necessary to develop a common design procedure to overcome these drawbacks. One of the common problems with newly introduced PM motors is the phenomenon of irreversible demagnetisation (ID) at high temperatures. So, a solution to this problem will be presented. The recently introduced ring winding axial flux PM (RWAFPM) motor is considered as a case study. First, a modified approach for modelling ID is introduced. Then, the effect of rotor geometry parameters on the ID of the RWAFPM motor is discussed. Finally, developed multi‐level multi‐objective design optimisation considering ID is presented based on the developed Taguchi method.